The Rise of Robotization During COVID-19 - Zuzanna BORDA; Jacek WINIARSKI (Communications of International Proceedings, 2021)
The article presents the research about the phenomenon of replacing human work with machines, called robotization of the workplaces. Researchers analyzed levels of unemployment in Poland and how it changed during the COVID-19 pandemic. The COVID-19 pandemic has resulted in growth in this area due to numerous lockdowns around the World. There is a demand for robots that can replace essential workers and help disinfecting the areas that could possibly be exposed to the virus. The article shows the research that help understand how robots work in the current labor market and that they can provide new workplaces and job opportunities for people, while replacing or enhancing their work.
Keywords: Robotization; Unemployment; COVID-19 Pandemic